PENGEMBANGAN BAHAN AJAR MICROSITE BERBASIS DIGITIAL MULTIWEB PADA MATA PELAJARAN IPAS - Muttaqin, Farid; Oktaviani Adhi Suciptaningsih; Riska Pristiani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop interactive learning media based on MultiWeb Microsite on Human Respiratory System material for grade V elementary school students. The development process adopts the DDD-E model (Decide, Design, Develop, Evaluate), with products that include teaching modules, assessments (diagnostic and formative), learning materials, LKPD, educational videos, and reflections-all packaged in a digital format that is responsive and easily accessible. Validation by material, language, and media experts showed a validity level of 92% (category “Very Valid”). Practicality tests showed positive responses from students (95%) and teachers (88.18%), both in the “Highly Practical” category. The effectiveness test showed that 84% of students achieved learning completeness in the “Very Good” category. These results indicate that MultiWeb Microsite-based learning media is feasible to use as an innovative, practical, and effective learning resource in IPAS learning at the elementary school level, especially on the topic of the human respiratory system.